2021
DOI: 10.3390/life11040362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Blood Levels of C-Reactive Protein Marker in Obstructive Sleep Apnea: A Systematic Review, Meta‐Analysis and Meta-Regression

Abstract: (1) Introduction: High sensitivity C-reactive protein (hs-CRP) and CRP are inflammatory biomarkers associated with several inflammatory diseases. In both pediatric and adult individuals with Obstructive Sleep Apnea (OSA) higher hs-CRP and CRP were observed, compared to controls. With the present systematic review, meta-analysis and meta-regression we expand upon previous meta-analyses in four ways: (1) We included 109 studies (96 in adults and 13 in children); (2) we reported subgroup and meta-regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 141 publications
1
16
0
Order By: Relevance
“…C-reactive protein (CRP) is an inflammatory biomarker associated with untreated OSA [50] which decreased shortly after the initiation of CPAP treatment [51]. CRP has recently been assessed as a risk factor for OSA in four prospective studies in population cohorts.…”
Section: Epidemiology Of Driving Accidents In the General Population ...mentioning
confidence: 99%
“…C-reactive protein (CRP) is an inflammatory biomarker associated with untreated OSA [50] which decreased shortly after the initiation of CPAP treatment [51]. CRP has recently been assessed as a risk factor for OSA in four prospective studies in population cohorts.…”
Section: Epidemiology Of Driving Accidents In the General Population ...mentioning
confidence: 99%
“…Several factors including environmental and genetic factors, and even internal conditions (hormones, cytokines, and other biomarkers), might lead to the emergence and maintenance of OSA. Smoking [ 12 ] and alcohol consumption [ 13 ], and alterations in the blood levels of intercellular adhesion molecule-1 [ 14 ], monocyte chemoattractant protein-1 [ 15 ], adiponectin [ 16 ], C-reactive protein [ 17 ], cortisol [ 18 ], interleukin-6 [ 19 ], tumor necrosis factor-alpha [ 20 ], astrocytic protein (S100B) [ 21 ], neuron-specific enolase [ 21 ], and polymorphisms [ 22 , 23 , 24 ] were observed among adults with OSA, compared to healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown the impact of ethnicity on the prevalence and severity of OSA that this impact can be related to ethnic differences in adipose tissue distributions [ 7 ]. Apart from the environmental and demographical factors, the studies reported that genetic [ 8 , 9 , 10 , 11 ] and blood [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] factors could also affect the prevalence or development of OSA.…”
Section: Introductionmentioning
confidence: 99%